The Trade Union Movement. Speech to the students of the Yale Divinity School (The Senior Class of the Sheffield Scientific School Yale Univerity)
The Yale scientific monthly. Facsimile reprint: New York, Arno Press & The New York Times, 1970. (American labor. From conspiracy to collective bargaining. Advisory editors: L. Stein and Ph. Taft). In: Wages, hours, and strikers: ...